The girl who threw butterflies - Cochrane, Mick (Alfred A. Knopf, 2009)
Eighth-grader Molly's ability to throw a knuckleball earns her a spot on the baseball team, which not only helps her feel connected to her recently deceased father, who loved baseball, it helps in other aspects of her life, as well.